A novel application of the EWMA Wilcoxon signed-rank control chart in the animal feed industry - Herdiani, Erna Tri; Masa, Mellyana; Jaya, Andi Kresna (Edelweiss Applied Science and Technology, 2025)
Control charts are essential tools in analysis and decision-making for quality control in production processes. This study aims to develop and evaluate the performance of the Exponentially Weighted Moving Average (EWMA) Wilcoxon Signed-Rank nonparametric control chart in monitoring the fat content of animal feed products, specifically at PT Japfa Comfeed Indonesia Tbk Makassar Unit. This study introduces the EWMA Wilcoxon Signed-Rank method as a nonparametric alternative to address the limitations of the classical EWMA, which relies on the assumption of normal distribution. A comparison was conducted with the EWMA Sign control chart to assess its effectiveness in detecting process anomalies with λ parameter variations of 0.05, 0.3, and 0.8. The results indicate that the EWMA Wilcoxon Signed-Rank control chart demonstrates superior anomaly detection capability compared to the EWMA Sign control chart for all tested λ values. This method is more effective in identifying small changes in the animal feed production process. The conclusion of this study is that the EWMA Wilcoxon Signed-Rank control chart has proven to be a more reliable tool for quality control in the animal feed industry. Implementing this method can enhance accuracy in detecting process deviations, thus helping companies maintain product quality consistency.